D’une capitale, l’autre. De Valladolid à Mexico au xvie siècle - Thomas Calvo (Les Cahiers de Framespa)
I met Bartolomé Bennassar in the first place for his masterpiece, Valladolid au Siècle d’Or. If there is any american city, at that time, which can be compared with this town, it is Mexico. The temptation is strong, then, to compare Valladolid au Siècle d’Or with the description made in 1554 by Francisco Cervantes de Salazar of his capital.